2012
DOI: 10.1016/j.imlet.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Potential role for alternatively activated macrophages in the secondary bacterial infection during recovery from influenza

Abstract: Purpose Secondary bacterial infections are a common complication of influenza. Innate immune host defenses appear to be impaired following influenza, leading to susceptibility to subsequent bacterial infections. Alternatively activated macrophages (AAM) in the lungs may play a critical role in eliciting the hypersusceptibility to secondary bacterial pneumonia. Methods C57BL6 mice were challenged with sublethal doses of the mouse-adapted A/PR/8/34 (PR8) influenza virus or saline and allowed to recover. At com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 35 publications
2
59
0
1
Order By: Relevance
“…Because viruses such as HIV and RSV altered activation statuses in macrophages (16)(17)(18)(19), we examined whether PRRSV infection interacts differentially with macrophages at different activation statuses. PRRSV infection induced differential cytokine responses in Ms polarized with different mediators (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because viruses such as HIV and RSV altered activation statuses in macrophages (16)(17)(18)(19), we examined whether PRRSV infection interacts differentially with macrophages at different activation statuses. PRRSV infection induced differential cytokine responses in Ms polarized with different mediators (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies here integrate antiviral regulation into the paradigm of activation statuses in porcine monocytic cells, a group of immune cells that not only are critical for overall immune responses but also are targeted by numerous economically devastating viruses to evade antiviral immunity (16)(17)(18)(19)21). These monocytotropic viruses include many of the world's most dreaded porcine viruses, such as African swine fever virus (ASFV), classical swine fever virus (CSFV), porcine circovirus 2 (PCV2), foot-and-mouth disease virus (FMDV), pseudorabies virus (PrV), swine influenza virus (SIV), and the focus of our studies, PRRSV (19,21,24,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pathway of infectioninduced Arg1 expression in the lung myeloid cell compartment was also observed in the current study in response to Spn, where we observed an infection dose dependent increase in Arg1 mRNA and protein levels in Spn-infected mice. On the other hand, Arg1-expressing alternatively activated macrophages have recently been shown to limit the severity of influenza infection in mice previously colonized with Spn [29], and the virulence factor Ply of Spn has been implicated in the generation of Arg1-expressing alternatively activated macrophages [30]. In this report, Spn-induced Arg1 expression, which was particularly observed in exudate rather than alveolar macrophages, did not impair lung antibacterial immunity against Spn, as Spn-infected WT mice had similar bacterial loads in their lungs as compared to Spn-infected conditional Arg1 KO mice.…”
Section: Discussionmentioning
confidence: 99%